The reaction of wheat cultivars to common root rot - Diehl, J. A. (Pesquisa Agropecuaria Brasileira, 2014)
In 1980 and 1981, 160 wheat (Thiticum aestivum L) cultivars and lines were tested at the Centro Nacional de Pesquisa de Trigo, at Passo Fungo, RS, Brazil, under field conditions, to determine their resistance to common root rot caused by Cochliobolus sativus. Cultivars and lines from Canada and United States, cited as resistant to this disease in those countries were included in the test. Under the experiment conditions, all cultivars and lines tested were very susceptible to common root rot.